Religious Education Curriculum Development: Between Islamic Boarding Schools, Schools, and Madrasahs - khakim, dzikrul; Ahid, Nur; Haq, Fikri Zakia Qoimul (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
The curriculum plays a central role in educational institutions because it refers to the direction, content and process of education, which ultimately determines the nature and qualifications of graduates of these educational institutions. There are at least three institutions that are well known to the public in Indonesia, including pesantren, schools and madrasah, each of which has its own characteristics. This study discusses the curriculum development of Islamic boarding schools, madrasah and schools. With the aim to know how the development. The method used in this research is a qualitative approach that focuses on library research. The results of the research show that the development of a religious education curriculum in pesantren, schools and madrasas involves a complex and contextual process. The curriculum is designed to cover an understanding of religious teachings, worship practices, ethics, morals, and the application of religious values ​​in everyday life. Islamic boarding schools, schools and madrasas apply various strategies in implementing the religious education curriculum. Nevertheless, there are several challenges in the development of the religious education curriculum. Some of these challenges include the diversity of students, social and cultural changes, lack of resources, and the integration of religious education with the general curriculum. In order to overcome these challenges, it is necessary to make collaborative efforts between pesantren, schools and madrasas by involving relevant stakeholders. It is also necessary to periodically update curriculum content so that it remains relevant to the times and the needs of students.